Distance and Isolation. The Role of Australia in Wojciech Gutkowski’s Colonial Dream in Journey to Kalopeia - Łukowska, Maria (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
This contribution is an attempt at a different reading of Wojciech Gutkowski’s Journey to Kalopeia (1817), which may be of interest to both Polish and Australian readers in the twenty-first century, since it tries to connect Polish history with the dream of the Antipodes represented by Australia. Gutkowski’s book, unknown until 1913, when it was deemed a utopian novel of little scientific value, gained recognition in the 1950s, 1960s, 1970s and 1980s. At that time it was studied as a political treatise and an Enlightenment model for the creation of an ideal utopian-socialist-communist state. This paper offers a new reading of the work in question, discussing its cultural-historical aspects as a precursor of a specifically Polish model of a utopian-colonial state.